The SSM at 1 - Luc Laeven; Mario Draghi; Andreas Dombret; Ignazio Angeloni; Sergio Nicoletti-Altimari; Felix Hufeld; Ludger Schuknecht; Hendrik Ritter; Christian Thimann; Josef A. Korte; Sascha Steffen; Emilio Barucci; et al. (SUERF - The European Money and Finance Forum, 2016)
On February 3-4, 2016 SUERF – The European Money and Finance Forum –, Deutsche Bundesbank and Stiftung Geld und Währung jointly organized a Colloquium/Conference in Frankfurt in order to evaluate the experience with the SSM – the Single Supervisory Mechanism – during the first year of its existence. The present issue of SUERF Conference Proceedings includes a selection of papers based on the authors' contributions to the Frankfurt event.
Keywords: E50; E52; E58; E65; F33; F36; F42; G21; G22; G28; G32; K33; O16; O17; O52; 330